THE EFFECTIVENESS OF USING THE DRILLING TECHNIQUES AND COLOR LETTER SORYBOARDING IN IMPROVING THE GRAMMAR SKILLS-AFFIXATION AMONG STUDENTS OF SPECIAL EDUCATION (Proceedings of International Conference on Special Education, 2015)
This study is an action research on the use of drilling technique are applied in teaching and learning in the classroom. Students found to have the skills to spell but have difficulty in pronunciation of words involves affixation. The study involved a student in category learning disabilities under the Special Education Program Integration with Learning Disabilities (PPKIBP) at SMK Pulau Tawar, Jerantut, Pahang. This study was conducted within 2 months of 6 cycles. Observation, document analysis and interviews were used to collect data. Data was analyzed using content analysis and pattern analysis. Triangulation and time used to interpret the data revision process. Analysis of the data showed the drilling technique using coloured letter telling point positive impact in terms of improving the terms of remuneration on the basis of words and subsequently produce derivatives in teaching and student learning while improving the practice as a teacher and researcher.